2016
DOI: 10.1038/srep20090
|View full text |Cite|
|
Sign up to set email alerts
|

Expression of programmed death ligand-1 on tumor cells varies pre and post chemotherapy in non-small cell lung cancer

Abstract: The effects of treatments to programmed death ligand-1 (PD-L1) expression is unknown. The aim of this study was to investigate the impact of neoadjuvant chemotherapy (NACT) on PD-L1 expression in non-small cell lung cancer (NSCLC) patients. PD-L1 expression was detected by immunohistochemistry (IHC) method in 32 paired tumor specimens pre and post-NACT. The positivity of PD-L1 on tumor cells (TCs) changed from 75% to 37.5% after NACT (p = 0.003). Cases with IHC score of 1, 2, 3 all underwent apparent decrease … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
138
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(146 citation statements)
references
References 41 publications
6
138
0
2
Order By: Relevance
“…Furthermore, previous studies have used different antibodies and various cut-offs to define high and low expression of PD-L1 and PD-1, respectively, making it problematic to compare the results. Finally, several factors have been reported to affect the expression of PD-1 and PD-L1, including chemotherapy 52 , 53 and radiotherapy. 22 However, in the present cohort, only 61 (29,8%) of patients with rectal cancer received neoadjuvant treatment, and we found similar results regarding the prognostic value of the investigated biomarkers when excluding neo-adjuvant treated rectal cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, previous studies have used different antibodies and various cut-offs to define high and low expression of PD-L1 and PD-1, respectively, making it problematic to compare the results. Finally, several factors have been reported to affect the expression of PD-1 and PD-L1, including chemotherapy 52 , 53 and radiotherapy. 22 However, in the present cohort, only 61 (29,8%) of patients with rectal cancer received neoadjuvant treatment, and we found similar results regarding the prognostic value of the investigated biomarkers when excluding neo-adjuvant treated rectal cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…Beyond anticipated gastrointestinal and cutaneous toxicities, the emergence of serious neurologic events related to pareneoplastic syndromes affecting central and peripheral nervous systems, deserves attention. A fatal event of myasthenia gravis with combination therapy and three cases of limbic encephalitis (two in the monotherapy and one in the dual regimens) were reported, one of which, occurring in the monotherapy arm, was grade 4 and resistant to steroid administration.Cytotoxic treatment and radiotherapy can promote antigenic exposure and microenvironment remodeling, favoring immune checkpoint inhibitor activity 18,81,82. A randomized phase II study (STIMULI, NCT02046733) is evaluating the impact of combined ipilimumab-nivolumab on OS after completion of standard chemoradiation in LD-SCLC(Table 2).…”
mentioning
confidence: 99%
“…11 Not only is the assumption concerning the theoretical cellular distribution of PD-1, PD-L1 and PD-L2 partial and imprecise, 12 but in addition their expression is M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT 5 prone to dynamic induction, notably upon exposure to cytokines such as interferon gamma. 13 Moreover, spatial, 14,15,16 temporal and therapeutic 17,18 factors can impact PD-L1 expression in the tumor microenvironment. All these elements highlight the dynamic nature of PD-L1 and cloud a clear understanding of PD-1/PD-L1 blockade mechanisms.…”
mentioning
confidence: 99%
“…Furthermore, there is clear plasticity in PD-L1 expression. Several studies across several tumor types have shown changes in PD-L1 expression on tumor cells after treatment with chemotherapy, begging the question of how to best pair or sequence chemotherapies to upregulate PD-L1 expression and enhance efficacy of checkpoint inhibition [17].…”
mentioning
confidence: 99%